Patterns of investment in agricultural research and innovation for the Global South, with a focus on sustainable agricultural intensification - Prasad, P. V. Vara; Bhatnagar, Nirat; Bhandari, Vineet; Jacob, George; Narayan, Kaushal; Echeverría, Ruben; Beintema, Nienke; Farah Cox, Paul; Compton, Julia (Frontiers in Sustainable Food Systems, 2023)
This study is the first attempt to determine global investment patterns for research and innovation in agriculture systems for the Global South, and specifically for innovation funding targeted at sustainable agricultural intensification. We analyzed and modeled patterns of funding from governments in the Global South, development partners, private companies, and private equity and venture capital funds, using primary and secondary sources of data spanning 2010 to 2019. We ascertain the key providers and recipients of innovation funding and how it is shared out between different topics and value chains. Results showed that about 60 billion of funding (ranging from 50 to 70 billion) goes toward agricultural innovation for the Global South each year, with 60–70% of it coming from these countries’ own governments (and the government of China accounting for as much as all others combined). This 60 billion investment represents just 4.5% of Global South agricultural output. Furthermore, less than 7% of the total funding was found to have detectable environmental intentions, and less than 5% had both social and environmental intentions. Adopting a standard for transparent reporting and measurement could potentially lead to swift changes in funding patterns towards sustainability goals.